Application of the Brook Rearrangement in Tandem with Single Electron Transfer Oxidative and Radical Processes. Issue 19 (31st March 2020) - Klychnikov, Mikhail K.; Pohl, Radek; Císařová, Ivana; Jahn, Ullrich
Abstract : Merging rearrangement with radical reactions is a largely unexplored field but may hold promise for approaching scaffolds that are inaccessible by other methodology. Here a tandem nucleophilic substitution/Brook rearrangement/single‐electron transfer oxidation/radical oxygenation strategy is presented, through which α, γ‐dioxygenated ε, ζ‐unsaturated amides are efficiently prepared in a single step from enantiomerically enriched allylepoxides and 2‐silylacetamides. The resulting compounds can be easily transformed by persistent radical effect‐based 5‐ exo ‐ trig or 6‐ endo ‐ trig radical cyclization reactions to functionalized carbocycles bearing three or four stereocenters. The stereochemical outcome of the cyclization reactions can predicted by the Beckwith–Houk model. The cyclic compounds can be easily diversified by post‐cyclization modifications. The tandem process can be further extended by an acylation step leading to β‐dicarbonyl enolates, which were also transformed to cyclopentane and cyclohexane derivatives under oxidative conditions. Abstract : Rearrangement and radical puzzle: Chiral epoxides, silylated acetamides, and stable radical TEMPO provide, with the help of ferrocenium hexafluorophosphate, dioxygenated carbonyl compounds, which serve as versatile radical cyclization precursors.